Prediction of cavitation and particle erosion in a radial divergent test section - Kevorkijan, Luka (JET on-line, 2022)
The 3D unsteady, cavitating, particle-laden flow through a radial divergent test section was simulated with the homogeneous mixture model and Discrete Phase Model (DPM) within the commercial CFD code ANSYS Fluent. For turbulence, a RANS approach was adopted with the Reboud’s correction of turbulent viscosity in the k-? SST model. Cavitation erosion was predicted with the Schenke-Melissaris-Terwisga (SMT) model, while particle erosion was predicted with the Det Norske Veritas (DNV) model. Two distinct erosion zones were identified, one for pure cavitation erosion and one for pure particle erosion. The occurrence of the pure particle erosion zone downstream of the cavitation erosion zone was analysed. By observing the streamlines downstream of the cavitation structures, it was found that vortices form in the flow and redirect the particles towards the wall, causing a pure particle erosion zone on the wall. Particles under consideration in this study were not found to alter the flow to the extent that the cavitation erosion zone would be significantly altered compared with the results without solid particles which are reported in the literature.
Keywords: cavitation; CFD; delci ANSYS Fluent; DPM; erosion; erozija; kavitacija; modeliranje; modelling; Particles ANSYS Fluent; RDT